Evaluation of Carrot Cultivars for Higher Growth, Yield and Postharvest Quality - Islam, Akimul; Rashid, Md Harun Ar; Hossain, Md Mokter; Rabbani , Md Golam; Zahura, Mst Fatema Tuz (Journal of the Bangladesh Agricultural University, 2025)
An experiment was conducted at the Horticulture Farm of the Bangladesh Agricultural University, Mymensingh during the period from October, 2023 to February, 2024 for evaluation of carrot cultivars for higher growth, yield and postharvest quality. The experiment consisted of twelve cultivars viz. Kuroda, New Kuroda, Kuroda 35, King Kuroda, Improved Shin Kuroda, Kuroda Improved, Shidur, Pusha Keshor, Bankim Keshor, BAU Gazor 5, Brasilia Agroflora and Prima Agroflora. The single factor experiment was laid out in Randomized Complete Block Design with three replications. Significant variation was observed for all the parameters studied. At 70 DAS, the highest plant height (81.33 cm), number of leaves per plant (12.20) were obtained from Pusha Keshor. The maximum root length (15.93 cm), root diameter (4.78 cm), fresh root weight (204.40 g), yield per plot (1.72 kg), gross yield of root (17.17 t/ha) and marketable yield of root (14.75 t/ha) were obtained from King Kuroda and dry mater content root (11.46%) were obtained from kuroda 35. In case of postharvest performance, maximum TSS content (20.20% brix), weight loss (46.19 %), was obtained from BAU Gazor 5, the highest disease incidence (60%) was found in Kuroda, whereas the maximum disease severity (54%) was observed in King kuroda and no disease incidence and severity were recorded in Improved Shin Kuroda, Bankim Keshor, Brasilia Agroflora and Prima Agroflora and the highest shelf life (12 days) was obtained from Improved shin kuroda. Therefore, it can conclude that G4 (King Kuroda) was found to be better in respect of higher growth, yield and quality and G5 (Improved Shin Kuroda) for better postharvest performance compared to other cultivars. J Bangladesh Agril Univ 23(3): 342–358, 2025